Discrete bin temperatures calculated from carbonate clumped isotope measurements performed on middle Miocene ODP Site 122-761B - Sevasti Modestou; Thomas Jan Leutert; Alvaro Fernandez; Caroline H Lear; Anna Nele Meckler (PANGAEA, 2020)
This table includes temperatures calculated from carbonate clumped isotope measurements performed on middle Miocene ODP Site 761B benthic foraminifera. A discrete binning method has been applied to the data presented here (as opposed to a probabilistic Gaussian window filter) This data is an accompaniment to the manuscript "Warm middle Miocene Indian Ocean bottom water temperatures: comparison of clumped isotope and Mg/Ca records", Paleoceanography and Paleoclimatology, submitted.
In: Modestou, S et al. (2020): Middle Miocene bottom water carbonate clumped isotope and Mg/Ca temperatures, ODP Site 122-761B, Indian Ocean [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.914309